A numerical study on hydrogen blending in natural gas pipeline by a T-Pipe - Xin Ouyang; Qiao He; Chong Chai; Yeqin Wang; Tao Di; Jingwei Zhou; Xu Sun (Journal of Pipeline Science and Engineering, 2024)
In order to study the flow blending and transporting process of hydrogen that injects into the natural gas pipelines, a three-dimensional T-pipe blending model is established and the flow characteristics are investigated systematically by the large eddy simulation (LES). Firstly, the mathematical formulation of hydrogen-methane blending process is provided and the LES method is introduced and validated by a benchmark gas blending model having experimental data. Subsequently, the T-pipe blending model is presented, and the effects of key parameters, such as the velocity of main pipe, hydrogen blending ratio, diameter of hydrogen injection pipeline, diameter of main pipe and operating pressure on the hydrogen-methane blending process, are studied systematically. The results show that, under certain conditions, the gas mixture will be stratified downstream of the blending point, with hydrogen at the top of the pipeline and methane at the bottom of the pipeline. In the no-stratified scenario, the mixing distance increases at lower hydrogen mixing ratio and larger diameter of the hydrogen injection pipe or the main pipe. Finally, based on the numerical results, the underlying physics of the stratification phenomenon during the blending process are explored and an indicator for stratification is proposed using the ratio between the Reynolds numbers of the natural gas and hydrogen.